The Transformation of Reason: Studies on System, Myth, and History in German Idealism - Ferrer, Diogo, (Critical Studies in German Idealism ;, 2024)
Critique, skepticism, conflict, incompleteness, nothingness, irrational abyss, evil, and even genocide... That is what German idealism is also about. Trying to chart human reason as an architectural system, Kant, Fichte, Hegel, and Schelling uncov